Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)
fs-ref-orig: Société santé en français. (2012). Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée. fs-code-orig: Société Santé en français-2014

Sensibilisation, structuration et consolidation en santé en français : 10 ans d’action - Société Santé en français (Reflets, 2014)

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)
fs-ref-orig: Vézina, S. et Doiron Robichaud, J. (2011). Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action. Bureau d’appui aux communautés de langue officielle de Santé Canada. http://docplayer.fr/123792385-Vers-une-demarche-concertee-pour-le-renforcement-de-la-recherche-sur-les-langues-officielles-dans-le-secteur-de-la-sante-bilan-et-pistes-d-action.html fs-code-orig: Vézina-2011